The case for home based telehealth in pediatric palliative care: a systematic review - Bradford Natalie; Armfield Nigel R; Young Jeanine; Smith Anthony C (BMC Palliative Care, 2013)
Abstract Background Over the last decade technology has rapidly changed the ability to provide home telehealth services. At the same time, pediatric palliative care has developed as a small, but distinct speciality. Understanding the experiences of providing home telehealth services in pediatric palliative care is therefore important. Methods A literature review was undertaken to identify and critically appraise published work relevant to the area. Studies were identified by searching the electronic databases Medline, CINAHL and Google Scholar. The reference list of each paper was also inspected to identify any further studies. Results There were 33 studies that met the inclusion criteria of which only six were pediatric focussed. Outcome measures included effects on quality of life and anxiety, substitution of home visits, economic factors, barriers, feasibility, acceptability, satisfaction and readiness for telehealth. While studies generally identified benefits of using home telehealth in palliative care, the utilisation of home telehealth programs was limited by numerous challenges. Conclusion Research in this area is challenging; ethical issues and logistical factors such as recruitment and attrition because of patient death make determining effectiveness of telehealth interventions difficult. Future research in home telehealth for the pediatric palliative care population should focus on the factors that influence acceptance of telehealth applications, including goals of care, access to alternative modes of care, perceived need for care, and comfort with using technology.